SELF-REGULATORY SYSTEMS: SELF-REGULATION AND LEARNING - Matric, Maja (Journal of process management and new technologies, 2018)
Self-regulation provides individuals the necessary means to achieve goals which can either arise from their own interests or societal demands. In both cases, achieving goals will enable individuals to experience self-fulfilment and success. Self-regulatory systems also maintain our actions within the limits of acceptable as well as restrain from unwanted behaviours. Self-regulatory learning helps learners achieve higher academic goals as it gives students control over their learning. In order to successfully self-regulate one's learning, it is important to recognize the essential components of self-regulatory learning, which help chose learning methods and strategies. We aimed at discovering which learning strategies and styles the students prefer and which elements of self-regulatory learning occur in the learning process. We can conclude that the students lack the knowledge of self-regulatory processes and learning strategies, and are unaware of their preferred learning styles.